Contemporary Dalit Assertions in Kerala: Governmental Categories vs Identity Politics? - J. Devika (History and Sociology of South Asia, 2013)
Caste inequality is a heatedly debated issue in contemporary Kerala, in stark contrast to an earlier time, when the idea that Kerala had overcome caste hierarchies through the twin strategies of social development and political mobilisation was still hegemonic. Post-1990s, political developments have pushed the question of caste back into the forefront of public debate, and ‘Dalit identity politics’ has been perceived as a serious threat by Kerala’s powerful left parties, despite the fact that Dalit political formations are not numerically powerful. Three processes seem to be crucial in precipitating the current situation: (a) the transformation of politics itself in the mid-1990s from the ‘public action’ mode to the ‘liberal’ mode, which was rejected by the Dalits and tribal communities; (b) rapidly widening economic inequalities and rapidly crystallising elite ideological dominance led to the strengthening of abjection as a mode of marginalisation of the lower castes which is being resisted; (c) the transformation of the Malayali literary public brought to the fore questions of caste and gender that were submerged under the earlier socio-cultural consensus generated by the hegemonic Malayali national popular shaped by the communists.